Family Business Governance and Outside Directors—Expectations from an Independent Director - Gallo, Miguel Angel (European Journal of Family Business, 2023)
Based on the author's own experience as an external and independent director of several boards of directors of family-owned companies, the objective of this paper is to show the responsibilities that these directors must assume and how they should preserve their qualities as "external" and "independent" directors. In this way, it is expected that this commentary can help to shape the procedure of incorporation and evaluation of external and independent directors.